The Elusive Origin of Atherosclerotic Plaque Calcification - Canet-Soulas, Emmanuelle; Bessueille, Laurence; Mechtouff, Laura; Magne, David (Frontiers in Cell and Developmental Biology, 2021)
It has been known for decades or even centuries that arteries calcify as they age. Vascular calcification probably affects all adults, since virtually all have atherosclerotic plaques: an accumulation of lipids, inflammatory cells, necrotic debris, and calcium phosphate crystals. A high vascular calcium score is associated with a high cardiovascular mortality risk, and relatively recent data suggest that even microcalcifications that form in early plaques may destabilize plaques and trigger a cardiovascular event. If the cellular and molecular mechanisms of plaque calcification have been relatively well characterized in mice, human plaques appear to calcify through different mechanisms that remain obscure. In this context, we will first review articles reporting the location and features of early calcifications in human plaques and then review the articles that explored the mechanisms though which human and mouse plaques calcify.